Heat Calculation of Borehole Heat Exchangers - S. O. Filatov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a heat calculation method of borehole heat exchangers (BHE) which can be used for designing and optimization of their design values and included in a comprehensive mathematical model of heat supply system with a heat pump based on utilization of low-grade heat from the ground.The developed method of calculation is based on the reduction of the problem general solution pertaining to heat transfer in BHE with due account of heat transfer between top-down and bottom-up flows of heat carrier to the solution for a boundary condition of one kind on the borehole wall. Used the a method of electrothermal analogy has been used for a calculation of the thermal resistance and  the required shape factors for calculation of  a borehole filler thermal resistance have been obtained numerically. The paper presents results of heat calculation of various BHE designs in accordance with the proposed method.